1986
DOI: 10.1104/pp.81.2.630
|View full text |Cite
|
Sign up to set email alerts
|

Differential Synthesis in Vitro of Barley Aleurone and Starchy Endosperm Proteins

Abstract: To widen the selection of proteins for gene expression studies in barley seeds, experiments were performed to identify proteins whose synthesis is differentially regulated in developing and germinating seed tissues. The in vitro synthesis of nine distinct barley proteins was compared using mRNAs from isolated endosperm and aleurone tissues (developing and mature grain) and from cultured (germinating) aleurone layers treated with abscisic acid (ABA) and GA3. B and C hordein polypeptides and the salt-soluble pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 20 publications
3
41
0
Order By: Relevance
“…It has been reported that storage proteins accumulate in the aleurone layer in rice and barley seeds. 14,15) These results suggest that globulin TBP has the role of seed storage protein, as well as albumin TBP.…”
Section: Discussionmentioning
confidence: 76%
“…It has been reported that storage proteins accumulate in the aleurone layer in rice and barley seeds. 14,15) These results suggest that globulin TBP has the role of seed storage protein, as well as albumin TBP.…”
Section: Discussionmentioning
confidence: 76%
“…Himalaya, 1985 harvest, Dept. of Agronomy, Washington State University, Pullman, WA) and treated with hormone as described previously (13,21). Vegetative and floral tissues for RNA extraction were dissected from 6-week-old, flowering Himalaya plants grown at 15°C in a greenhouse.…”
Section: Methodsmentioning
confidence: 99%
“…Blots were stringently washed at 65°C in 0.1 ϫ SSC, 0.1% SDS for 30 min prior to exposure. mRNA for cDNA library construction was isolated as described previously (21). Pooled mRNA templates for cDNA synthesis were extracted from aleurone layers incubated with or without 2 M GA and/or 20 M cycloheximide for 2, 6, 12, and 24 h. cDNA was synthesized by the RNase H method (26), ligated to EcoRI adaptors, and cloned in gt11.…”
Section: Methodsmentioning
confidence: 99%
“…This is generally true for a number of diverse plants, e.g., cotton (Galau et al, 1986), rapeseed (Finkelstein et al, 1985), rice (Mundy & Chua, 1988) and wheat (Quatrano, 1986). These include a \ectin (Raikbel & Wilkins, 1987), enzyme inhibitor (Mundy et al, 1986), lipid body membrane protein (Hatzopoulos et al, 1990) and storage proteins (Bray & Beacby, 1985;Finkelstein et al, 1985;Quatrano, 1986). In addition, a number of proteins called LEAs (Late £^mbryo Abundant proteins) from cotton, wheat (e.g., Em) and rice (e.g., RAB 17) were also found in mature seeds and could be induced precociously by ABA treatment.…”
Section: Ab A-r Esponsive Genesmentioning
confidence: 99%